EFEKTIVITAS STRATEGI THINK - TALK - WRITE TERHADAP KEMAMPUAN MENULIS SISWA PADA MATERI RECOUNT TEXT DI SMP DARUDDA'WAH - Aufi Dalida, Putri; Yolanda, Alvina; Ismu Purwaningsih, Dewi (Pengelola Jurnal Politeknik Negeri Ketapang, 2024)
One important English skill students need to master is writing, which helps them express their ideas in writing. However, many students find writing less interesting because it involves several steps and rules. Using effective strategies can improve these skills. The TTW (Think-Talk-Write) strategy is designed to motivate students and help them develop their ideas in writing recount texts.This research aims to see if the TTW strategy improves students' writing skills in recount texts. The study used an experimental method with a pre-test and post-test design. Data were collected through tests, rubrics, and observations. The results show that the TTW strategy increased students' writing abilities. In the study, 17 students from class VIII were given a pre-test, received TTW treatment, and then took a post-test. The test results, analyzed using a Paired Sample T-test in SPSS 23.0, showed an average pre-test score of 44.41 (SD = 14.349) and an average post-test score of 70.00 (SD = 13.229). The higher post-test score indicates that the TTW strategy significantly improved students' writing skills in recount texts.the Think-Talk-Write strategy is effective in enhancing students' abilities to write recount texts. It encourages students to write more and helps develop their creativity through thinking, talking, and writing.